2023
DOI: 10.3390/v15030610
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Study on Effectiveness of Molnupiravir and Nirmatrelvir–Ritonavir in Unvaccinated Patients with Chronic Respiratory Diseases with Confirmed SARS-CoV-2 Infection Managed in Out-Patient Setting

Abstract: While molnupiravir (MOV) and nirmatrelvir–ritonavir (NMV-r) were developed for treatment of mild to moderate COVID-19 infection, there has been a lack of data on the efficacy among unvaccinated adult patients with chronic respiratory diseases, including asthma, chronic obstructive pulmonary disease (COPD) and bronchiectasis. A territory-wide retrospective cohort study was conducted in Hong Kong to investigate the efficacy of MOV and NMV-r against severe outcomes of COVID-19 in unvaccinated adult patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The large differences in underlying study populations, outcome definitions and inclusion criteria can probably explain at least part of this heterogeneity. Some studies focused on specific patient groups such as patients with inflammatory bowel disease, 41 solid organ transplant patients, 42 patients with chronic respiratory disease, 44 systemic rheumatic disease, 55 diabetes, 47 hematological malignancy, 56,59 and long-term facility residents. 48,50 Inclusion and exclusion criteria were not uniform across studies, and neither were outcome definitions, especially for the outcome of "disease progression.…”
Section: Heterogeneity Of the Included Studiesmentioning
confidence: 99%
“…The large differences in underlying study populations, outcome definitions and inclusion criteria can probably explain at least part of this heterogeneity. Some studies focused on specific patient groups such as patients with inflammatory bowel disease, 41 solid organ transplant patients, 42 patients with chronic respiratory disease, 44 systemic rheumatic disease, 55 diabetes, 47 hematological malignancy, 56,59 and long-term facility residents. 48,50 Inclusion and exclusion criteria were not uniform across studies, and neither were outcome definitions, especially for the outcome of "disease progression.…”
Section: Heterogeneity Of the Included Studiesmentioning
confidence: 99%
“…17,18 Studies have shown that compared with molnupiravir, NMV-r may provide a greater clinical benefit by decreasing the likelihood of hospitalization or mortality. [19][20][21] In the EPIC-HR trial, NMV-r significantly reduced hospitalization and mortality rates in nonhospitalized patients with mild-to-moderate COVID-19 who were at a risk of severe disease. The drug was effective when initiated within 3 or 5 days of symptom onset, with reductions of 89% or 88%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two orally administered antiviral agents are available for nonhospitalized patients with COVID‐19 and those who are at high risk: a combination of nirmatrelvir and ritonavir (NMV‐r) and molnupiravir 17,18 . Studies have shown that compared with molnupiravir, NMV‐r may provide a greater clinical benefit by decreasing the likelihood of hospitalization or mortality 19–21 . In the EPIC‐HR trial, NMV‐r significantly reduced hospitalization and mortality rates in nonhospitalized patients with mild‐to‐moderate COVID‐19 who were at a risk of severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…9 In view of this evidence, the Food and Drug Administration and the European Medicines Agency issued in December 2021 and January 2022, respectively, the emergency use authorization (EUA) for NMV/r to treat mild-to-moderate laboratoryconfirmed COVID-19 in nonhospitalized patients at high risk of clinical progression, which include those who are immunocompromised. 10 In spite of the encouraging results from the EPIC-HR trial and the growing number of real-life studies performed in the general population, [11][12][13][14] the need of co-administration with ritonavir (a potent inhibitor of cytochrome CYP3A4) raises concerns about the potential for drug-to-drug interactions (DDIs) and associated adverse effects. 15 This circumstance has limited the use of NMV/r among patients receiving immunosuppressive therapies, thus narrowing their already limited options.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the encouraging results from the EPIC‐HR trial and the growing number of real‐life studies performed in the general population, 11–14 the need of co‐administration with ritonavir (a potent inhibitor of cytochrome CYP3A4) raises concerns about the potential for drug‐to‐drug interactions (DDIs) and associated adverse effects 15 . This circumstance has limited the use of NMV/r among patients receiving immunosuppressive therapies, thus narrowing their already limited options 16 .…”
Section: Introductionmentioning
confidence: 99%